Diversity and abundance of insect pollinators and visitors of Indian mustard (Brassica juncea L.) - Ramkumar, N; Vinita, S; Gouri, S G; Arvind, K; Ram, K; Srinivasa, N; Singh, A K; Kartikeya, S; Raju, S V S (Plant Science Today, 2026)
The study was conducted to identify the diversity and abundance of insect pollinators and floral visitors associated with Indian mustard (Brassica juncea). A total of 24 insect species were observed and collected in the study, which represented five insect orders, 14 families and 21 genera. The order Hymenoptera was the most dominant, accounting for 45.83 % of the total pollinators/visitors, with 11 species of eight genera, followed by order Diptera, contributing 29.16 % of the total insect assemblage with seven species from seven genera. Among all the insects, three species belonged to the order Lepidoptera from three genera (12.50 %), while Coleoptera, with 8.33 % of abundance, included two species from two genera and a single species of order Neuroptera was recorded with 4.16 %. Among the visitors, eight insect species were recorded as pollinators: Apis species, i.e. A. dorsata (32.9 %), A. cerana indica (22.9 %) and A. mellifera (18.7 %), followed by other hymenopteran Tetragonula iridipennis (9.4 %), which was most dominant, while the least dominant were Dipteran Eristalinus arovum (2.8 %). The pollinators had the peak period of activity between 11.00 am to 1.00 pm, where the mean population was 5.03 and the least activity was observed between 7.00 AM to 9.00 AM and 3.00 PM to 5.00 PM, with a mean population of 0.72 and 0.91 each. The findings reveal the predominance of Hymenopteran species in B. juncea along with other species, underscoring the need for pollinators in agroecosystems to affect the reproductive success and productivity of cross-pollinated crops like Indian mustard.